Internacionalismo y diplomacia sindical (1888-1986) - Aroca Mohedano, Manuela; Van Goethem, Geert; Domínguez Prats, Pilar; Romero, Frederico (Madrid: Catarata, 2019)
"Manuela Aroca Mohedano (dir.); Geert Van Goethem, Pilar Domínguez Prats, Frederico Romero, ... et al."